Modeling of Electron‐Transfer Kinetics in Magnesium Electrolytes: Influence of the Solvent on the Battery Performance. Issue 21 (7th October 2021) - Drews, Janina; Jankowski, Piotr; Häcker, Joachim; Li, Zhenyou; Danner, Timo; García Lastra, Juan Maria; Vegge, Tejs; Wagner, Norbert; Friedrich, K. Andreas; Zhao‐Karger, Zhirong; Fichtner, Maximilian; Latz, Arnulf
Abstract: The performance of rechargeable magnesium batteries is strongly dependent on the choice of electrolyte. The desolvation of multivalent cations usually goes along with high energy barriers, which can have a crucial impact on the plating reaction. This can lead to significantly higher overpotentials for magnesium deposition compared to magnesium dissolution. In this work we combine experimental measurements with DFT calculations and continuum modelling to analyze Mg deposition in various solvents. Jointly, these methods provide a better understanding of the electrode reactions and especially the magnesium deposition mechanism. Thereby, a kinetic model for electrochemical reactions at metal electrodes is developed, which explicitly couples desolvation to electron transfer and, furthermore, qualitatively takes into account effects of the electrochemical double layer. The influence of different solvents on the battery performance is studied for the state‐of‐the‐art magnesium tetrakis(hexafluoroisopropyloxy)borate electrolyte salt. It becomes apparent that not necessarily a whole solvent molecule must be stripped from the solvated magnesium cation before the first reduction step can take place. For Mg reduction it seems to be sufficient to have one coordination site available, so that the magnesium cation is able to get closer to the electrode surface. Thereby, the initial desolvation of the magnesium cation determines the deposition reaction for mono‐, tri‐ and tetraglyme, whereas the influence of the desolvation on the plating reaction is minor for diglyme and tetrahydrofuran. Overall, we can give a clear recommendation for diglyme to be applied as solvent in magnesium electrolytes. Abstract : Desolvation vs. electron transfer : The combination of DFT and continuum modeling techniques with experimental measurements sheds light on the magnesium deposition mechanism and the role of the involved solvent. Thereby, a new kinetic model for the electrochemical reaction is developed and general properties, which are crucial for fast kinetics and low overpotentials, are identified.